2005
DOI: 10.1191/0267659105pf828oa
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of conventional extracorporeal circulation and minimal extracorporeal circulation with respect to microbubbles and microembolic signals

Abstract: The intention of minimal extracorporeal circulation (MECC) is to reduce priming volume and minimize contact of blood with polymers and air in a closed system. In contrast to conventional extracorporeal circulation (ECC), a venous reservoir is missing. Thus, air trapping is limited and avoidance of bubble embolism is a major concern. This study investigates microbubbles (MBB) number and size in the venous and arterial lines of ECC and MECC compared to the number of microembolic signals (MES) in the right and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 14 publications
3
20
0
Order By: Relevance
“…In contrast to these experimental and our clinical findings, a reduction of cerebral microembolic load with MiECC has been demonstrated during CABG surgery (39,40). A similar trend was observed by a group studying the incidence of retinal microembolism in patients undergoing SAVR with CECC or MiECC.…”
Section: Discussionsupporting
confidence: 86%
“…In contrast to these experimental and our clinical findings, a reduction of cerebral microembolic load with MiECC has been demonstrated during CABG surgery (39,40). A similar trend was observed by a group studying the incidence of retinal microembolism in patients undergoing SAVR with CECC or MiECC.…”
Section: Discussionsupporting
confidence: 86%
“…Less arterial GME volume is seen in the mini-bypass system as compared to a conventional system, confirming the importance of having an active air management system on the venous side in any mini-bypass circuit. It should be noted that the same trend of GME at the outlet of the reservoir has been seen by our institution regardless of the type of open venous reservoir used [25].…”
Section: Discussionsupporting
confidence: 75%
“…In contrast, two recent studies reported a lower embolic load in patients perfused with a MECC system as compared to a conventional CPB system during CABG (10,11).…”
Section: Air Removal Efficiency Of a Venous Bubble Trap 1095mentioning
confidence: 78%